Karen Hess: The Carolina Rice Kitchen - The African Connection - Davidson, Alan E (Petits Propos Culinaires, 1992)
Karen Hess: The Carolina Rice Kitchen - The African Connection, incorporating in facsimile the Carolina Rice Cook Book (of 1901): University of South Carolina Press, Columbia SC, 1992: 224 pp, few b/w illustrations, extensive notes, bibliography, index, 24.95.